A transposição do acordo de leniência à lei anticorrupção: uma análise da adequação do instituto aos seus fundamentos com base nos conceitos microjurídicos de corrupção previstos no art. 5º da lei no 12.846/2013. - Aline Mello Terrão (2023)
The object of this dissertation is the study of the transposition of the leniency program of the Brazilian Competition Defense System (SBDC) into the anti-corruption system. In summary, it seeks to evaluate whether the adoption of the institute by Law No. 12,846/2013, also called Anti-Corruption Law (LAC), respected the logic underlying the program and, if so, whether the characteristics often associated with the effectiveness of the antitrust leniency program also candissuade acts of corruption provided for in Art. 5 of LAC. To achieve the proposed objective, a bibliographical research was carried out, from which it was concluded that the existence of multiple distinct relationships encompassed by the leniency program of the Anti-Corruption Law creates a problem of coordination of incentives. Today, as the instrument is designed, it is difficult to conclude if the program is effective. As possible solutions, it is suggested the elimination of the conditioned clause from item I of art. 16 of LAC and the production of economic studies that aims to identifying the effectiveness of anticorruption leniency program based on the micro-legal concepts of corruptions adopted in its art. 5th. .